Pretreatment maximum standardized uptake value in 18F-fluorodeoxyglucose positron emission tomography-computed tomography as a prognostic factor for ovarian clear cell carcinoma and low-grade serous carcinoma - Takuto Matsuura; Isao Otsuka; Toshihiro Ouchi; Eri Ouchi; Ryoko Asano; Naoyuki Miyasaka (Elsevier, 2021)
Objective: The maximum standardized uptake value (SUVmax) derived by positron emission tomography-computed tomography (PET/CT) can be an index of biological tumor aggressiveness, which is assessed using noninvasive tools before the treatment of epithelial ovarian cancer (EOC). This study aimed to evaluate the prognostic value of the pretreatment SUVmax in patients with EOC. Materials and methods: We reviewed the data of patients with EOC who underwent pretreatment 18F-FDG PET/CT between June 2006 and September 2016. The relationships between pretreatment SUVmax and histological subtypes of EOC were determined. Moreover, progression-free survival (PFS) and overall survival (OS) were evaluated according to the pretreatment SUVmax. Risk factors associated with progression or death were also analyzed. Results: Of 148 patients, 66 (44.6%), 11 (7.4%), 34 (23.0%), 19 (12.8%), 15 (10.1%), and three (2.0%) were diagnosed with high-grade serous carcinoma (HGSC), low-grade serous carcinoma (LGSC), clear cell carcinoma (CCC), endometrioid carcinoma, mucinous carcinoma, and others, respectively. The median SUVmax was marginally lower in LGSC (6.80 vs. 10.5; P = 0.059) and significantly lower in CCC (5.92 vs. 10.5; P = 0.001) than in HGSC. A high pretreatment SUVmax (≥9.30) was a prognostic factor for OS in patients with LGSC (P = 0.046). Furthermore, multivariate analysis revealed that a high SUVmax (≥5.85) was an independent prognostic factor for OS (P = 0.046) in patients with CCC. However, a high SUVmax (≥7.77) was a poor predictor of PFS and OS in patients with EOC (P = 0.156 and P = 0.158, respectively). Conclusion: Our findings suggest that the pretreatment SUVmax is not only an independent predictor of survival in patients with CCC but also a significant predictor of survival in patients with LGSC.